2020
DOI: 10.1159/000506628
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Indication for Advanced Gallbladder Cancer Considering the Optimal Preoperative Carbohydrate Antigen 19-9 Cutoff Value

Abstract: Background: Selecting patients who will benefit from resection among those with advanced gallbladder cancer (GBCa) having poor prognostic factors is difficult. Methods: One hundred twenty-one patients who underwent resection for stage II-IV GBCa and 19 unresected patients (unresectable group) were enrolled. The clinical impact of carbohydrate antigen 19-9 (CA19-9) and advanced surgical procedures for GBCa was evaluated. Results: The optimal CA19-9 cutoff value (based on the greatest difference in overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The T4 GBC has less benefit from lymph node dissection 39 . In another study the overall survival of patients who had CA19-9 more than 250 U/ml and underwent either major hepatectomy or PD had similar outcomes to the unresectable group 40 . The poor prognostic factors of T3/T4 GBD are liver invasion ≥5 mm, invasion of the left margin or the entire area of the hepatoduodenal ligament, and ≥4 regional lymph node metastases.…”
Section: Gallbladder Cancer Diagnosed Before Definitive Operationmentioning
confidence: 88%
“…The T4 GBC has less benefit from lymph node dissection 39 . In another study the overall survival of patients who had CA19-9 more than 250 U/ml and underwent either major hepatectomy or PD had similar outcomes to the unresectable group 40 . The poor prognostic factors of T3/T4 GBD are liver invasion ≥5 mm, invasion of the left margin or the entire area of the hepatoduodenal ligament, and ≥4 regional lymph node metastases.…”
Section: Gallbladder Cancer Diagnosed Before Definitive Operationmentioning
confidence: 88%
“…Yamamoto et al reported that the surgical outcome for patients with preoperative CA19‐9 values of 250 U/mL or higher was similar to that of non‐resected patients, and they stated that the indication for surgery in such patients should be carefully considered 22 …”
Section: Surgical Treatmentmentioning
confidence: 99%
“…21 Yamamoto et al reported that the surgical outcome for patients with preoperative CA19-9 values of 250 U/mL or higher was similar to that of non-resected patients, and they stated that the indication for surgery in such patients should be carefully considered. 22 Sahara et al developed the GBC recurrence risk (GBRR) score to predict early recurrence within 12 months using 309 cases from the US Extrahepatic Biliary Malignancy Consortium database. The risk of early recurrence can be evaluated from high to low by inputting preoperative CA19-9, with or without hemihepatectomy, T stage, and histological grade (12-month RFS; low risk: 88.4%, intermediate risk: 77.9%, high risk: 37.0%).…”
Section: Resectability Criteria For Locally Advanced Gbcmentioning
confidence: 99%